2006
DOI: 10.1080/15216540600838232
|View full text |Cite
|
Sign up to set email alerts
|

RNase L: Its biological roles and regulation

Abstract: Summary2 0 -5 0 oligoadenylate-dependent ribonuclease L (RNase L) is one of the key enzymes involved in the function of interferons (IFNs), a family of cytokines participating in innate immunity against viruses and other microbial pathogens. Upon binding with its activator, 5 0 -phosphorylated, 2 0 -5 0 linked oligoadenylates (2-5A), RNase L degrades single-stranded viral and cellular RNAs and thus plays an important role in the antiviral and antiproliferative functions of IFNs. In recent years, evidence has r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 40 publications
3
71
0
4
Order By: Relevance
“…The induction of apoptosis is still not elucidated by any mechanism. Activation of RNase L by 2-5A transfection into cells results in specific 18S rRNA cleavage and induction of apoptosis, which is company by cytochrome c release from mitochondria (19). In addition, induction of apoptosis by 2-5A can be blocked with pancaspase inhibitor Z-VAD-fmk or with caspase 3 inhibitor DEVD-fmk, suggesting the involvement of caspase in RNase L-mediated apoptotic pathway.…”
Section: Structure Of Abce1mentioning
confidence: 97%
“…The induction of apoptosis is still not elucidated by any mechanism. Activation of RNase L by 2-5A transfection into cells results in specific 18S rRNA cleavage and induction of apoptosis, which is company by cytochrome c release from mitochondria (19). In addition, induction of apoptosis by 2-5A can be blocked with pancaspase inhibitor Z-VAD-fmk or with caspase 3 inhibitor DEVD-fmk, suggesting the involvement of caspase in RNase L-mediated apoptotic pathway.…”
Section: Structure Of Abce1mentioning
confidence: 97%
“…Les ARN ribosomiques ont été une des premières cibles cellulaire identifiée de la RNase L. Leur clivage sert de témoin d'activation de la RNase L. La RNase L participe à la limitation de la réponse cellulaire à l'IFN en régu-lant la stabilité des ARNm de gènes induits par l'IFN : ISG15, ISG43 et PKR, [35,36]. Des variations d'expression d'IFN ou d'OAS lors de la croissance cellulaire, la différenciation, la régéné-ration hépatique, la sénescence sont connues depuis longtemps [21,22]. D'autre part, il a aussi été montré que l'OAS peut être activée par les séquences double brin des ARN cellulaires.…”
Section: Rnase L Et Arn Cellulairesunclassified
“…Other studies have demonstrated that PKR and RNaseL modulate WNV pathogenesis in mice by controlling infection in peripheral tissues and neurons [61]. Like PKR, RNaseL modulates mRNA translation but does so by cleaving target RNA substrates [62]. PKR and RNaseL deficient mice were significantly more susceptible to subcutaneous WNV infection than wild type mice, and exhibited increased viremia and viral burden in peripheral tissues in association with earlier entry of the virus into the brain and CNS [61].…”
Section: Isgs Control Hcv and Wnv Replicationmentioning
confidence: 99%